THE EFFECT OF DURATION REPLACEMENT FEED TIME Tubifex sp. WITH PASTA FEED ON GROWTH AND SURVIVAL RATE OF KOI (Cyprynus carpio) FISH LARVA - Fitri Merga Ayu; Sukendi Sukendi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe research was carried out for 40 days, from 10 May to 20 June 2019, at the fish hatchery and Breeding Laboratory Department of Aquaculture, Faculty of Fisheries and Marine. University of Riau. This study aims to determine the effect of the length of feed change time Tubifex sp. with the best pasta feed on the growth and survival of koi fish (Cyprinus carpio) larvae. That are kept for 40 days in an aquarium container size of 30x30x30 cm as many as 12 pieces, filled with water as much as 15 liters/container, densely stocked 2 fish/liter. The method used in this research was the experimental method. The design used was a Completely Randomized Design (CRD) one factor with 5 treatments and 3 replications.The treatments used were P1 (Tubifex sp. For 40 days), P2 (Tubifex sp. 10 days + 30-day Pasta ), P3 (Tubifex sp. 20 days + 20-day Pasta ), P4 (Tubifex sp. 30 days + Pasta 10 days), P5 (pasta for 40 days).The best growth research results was obtained in the treatment of P1 (Tubifex sp. For 40 days) with an average growth of absolute weight 3,43 grams, growth of absolute length 5,93 cm, specific growth rate of 13,84% /day. As for the variation of the best change of time, there were treatments in P4 (Tubifex sp. 30 days + 10day Pasta) with an average absolute weight growth of 2.97 grams, absolute length 5.31 cm, specific growth rate of 13.70% /day, for survival rate not significantly different for treatment. Water quality during the study was temperature ranging from 27-31 °C, pH 5,4-6,5 and DO of 4,1-5,2 ppm.Keywords : Feed Substitution, Tubifex sp., Pasta feed, koi fish (Cyprinus carpio) larvae, Growth, Survival Rate